UNDERSTANDING CONSUMER INTENTIONS AND PERCEPTIONS OF ELECTRONIC SCOOTERS: A STUDY AMONG WORKING WOMEN - G. Banupriya; V.Sengamalam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The growing popularity of electronic scooters (e-scooters) as a sustainable and convenient urban transportation option has drawn significant attention in recent years. Despite this trend, there is limited research focusing on the perspectives of specific demographic groups, particularly working women. This study explores the factors shaping working women’s intentions to use e-scooters, including convenience, cost, safety, environmental awareness, and societal attitudes. Using a mixed-methods approach that combines surveys and interviews, the research examines insights from women in both urban and suburban areas. The findings reveal a strong emphasis on safety and affordability, along with varying perceptions about the practicality of e-scooters for daily commutes. These results provide valuable recommendations for developing inclusive, gender-sensitive transportation policies and products.